ANALISIS KINERJA PEGAWAI DALAM PELAYANAN PUBLIK PADA KANTOR LURAH BANTUAS KECAMATAN PALARAN, KOTA SAMARINDA - Ayatullah Khumaini (Jurnal Paradigma (JP), 2017)
The aims of this research are to know employee permorfance and to identify the influence factors of enhancement employee performance in Bantuas, Samarinda. The result shows that employee performance in delivering public service can be seen from various aspects such as productivity and responsiveness. Productivity includes the degree of understanding to job description and attitude in delivery the services. Responsiveness includes the degree of respons of employee, the available chances for citizen to deliver their arguments and also spontaneous in handling the problems.